Progression in yield and value addition of Indian bread wheat – An analysis - Mohan, D.; Tiwari, V.; Gupta, R.K. (The Indian Journal of Genetics and Plant Breeding, 2017)
National wheat programme of India was examined forprogress made in yield and quality in ten differentproduction environments. During the period 2000-16,productivity improved in three environments namely timelysown condition of north-western plains zone (NWPZ) andtimely and late-sown wheats of central zone (CZ). Certainnon-grain parameters like plant height, vegetative periodand crop duration were the significant contributors in theseenvironments. Improvement in grain quality was zonespecific but simultaneous increase in productivity and valueaddition was witnessed in the most important region ofthe country i.e., NWPZ. Chapati quality and physical grainquality improved in the Indo-Gangetic plains and peninsularzone (PZ). Amongst the baked products; quality of thecookies was improvised in the hills whereas progress inbread loaf volume was visible in NWPZ and PZ. In qualitycomponents, protein content was enhanced in PZ andgluten characteristics were improved in NWPZ. Exceptreduction in bread quality score, no major change occurredin grain quality of the new varieties developed for hot anddry climate of central India.